An empirical study of worldwide governance indicators as determinants of debt maturity structure for public and private debt securities in Malaysia and Singapore - Abdul Wahab, Noor Maimun; Md Nassir, Annuar; Abdul Rahim, Norhuda; Ab Razak, Nazrul Hisyam; Mohd Hisham, Mohd Hizwan; Haron, Nurfaradilla; M. S., Senin (Department of Applied Linguistics, Translators and Interpreters, University of Antwerp, 2021)
This study examines worldwide governance indicators (WGI) as new potential additional determinants for debt maturity structure of public and private debt securities in Malaysia and Singapore. 745 listed Malaysian (537 listed firms) and Singaporean (208 listed firms) nonfinancial firms for the period of year 1996 until 2016 are utilizes in explaining the relationship between WGI and debt maturity structure. Overall, decision of Malaysian and Singaporean firms regarding their debt maturity structure in the past strongly influence by its current and future decision. Moreover, all elements in WGI are more important in influencing debt maturity structure of public or private debt securities in developing country like Malaysia as compared to developed country like Singapore. Finding of this study offers some policy implication as it assists in controlling and stimulating the firms’ demand for long-term public and private debt securities which contribute towards conducive and healthy business environment and maintain stable economic growth.